Dense granule protein 3 of Toxoplasma gondii plays a crucial role in the capability of the tissue cysts of the parasite to persist in the presence of anti-cyst CD8+ T cells during the chronic stage of infection - Mani, Rajesh; Abdelaziz, Mohamed H.; Ochiai, Eri; Sa, Qila; Fox, Barbara A.; Bzik, David J.; Suzuki, Yasuhiro (Frontiers in Immunology, 2023)
Toxoplasma gondii establishes chronic infection by forming tissue cysts, and this chronic infection is one of the most common parasitic infections in humans. Our recent studies revealed that whereas CD8 + T cells of genetically resistant BALB/c mice have the capability to remove the tissue cysts of the parasite through their perforin-mediated activities, small portions of the cysts are capable of persisting under the presence of the anti-cyst CD8 + T cells. It is currently unknown how those small portions of the cysts resist or escape the T cell immunity and persist in the hosts. In the present study, we discovered that the cysts, which persisted under the presence of the perforin-mediated CD8 + T cell immunity, have significantly greater mRNA levels for four dense granule proteins, GRA1, GRA2, GRA3, and GRA7, and one rhoptry protein, ROP35, than the total population of the cysts present in the absence of the T cells. In addition, increased levels of mRNA for GRA1, GRA3, and ROP35 in the cysts significantly correlated with their successful persistence through the condition in which greater degrees of reduction of the cyst burden occurred through anti-cyst CD8 + T cells. In addition, GRA3-deficient T. gondii displayed significantly enhanced elimination of the cysts by anti-cyst CD8 + T cells when compared to the wild-type parasite. These results indicate that GRA3 is a key molecule that mediates in the capability of T. gondii cysts to persist by resisting or evading the anti-cyst activity of CD8 + T cells during the later stage of infection.